A COMPARATIVE STUDY OF SHARIA ECONOMIC LAW AND ENGLISH COMMON LAW IN GOVERNING FINANCIAL CONTRACTS - Masyhur Masyhur; Maria Clara Reyes; Ruby King (Yayasan Adra Karima Hubbi, 2025)
The proliferation of hybrid financial contracts, intended to be Sharia-compliant yet governed by English Common Law, creates significant legal ambiguities and conflicts regarding their enforceability. This study conducts a comparative doctrinal analysis to identify foundational conflicts between Sharia Economic Law and English Common Law, and to critically examine the judicial interpretation of these hybrid instruments by English courts. The research employs a qualitative, doctrinal methodology. A comparative analysis of primary legal sources including fiqh texts, statutes, AAOIFI standards, and key judicial precedents was conducted, anchored by landmark case law analysis. The findings reveal a fundamental, non-convergent divergence, particularly regarding riba (interest) and gharar (uncertainty). The analysis confirms English courts prioritize the explicit “governing law” clause over Sharia compliance, creating a significant ‘enforcement gap’ where contractual intent is superseded by Common Law remedies. This study concludes that the prevailing legal hybridity model functions as a ‘legal fiction,’ posing systemic risks to the Islamic finance industry’s integrity. It demonstrates that the “nesting” of Sharia within Common Law is unsustainable, necessitating new “trans-systemic” legal frameworks.